Intra-Day and Inter-Day Reliability of Measurements of the electromyographic signal on masseter and temporal muscles in patients with Down syndrome - Giannasi, Lilian Chrystiane [UNESP]; Politti, Fabiano; Dutra, Marignês T. S. [UNESP]; Tenguan, Vera L. S. [UNESP]; Silva, Gabriela R. C. [UNESP]; Mancilha, Gabriela P. [UNESP]; Silva, Daniel Batista da [UNESP]; Oliveira, Luis Vicente Franco; Oliveira, Claudia Santos; Amorim, Jose B. O. [UNESP]; Salgado, Miguel Angel Castillo [UNESP]; Gomes, Mônica F. [UNESP] (Springer Nature, 2020)
The aim of the present study was to evaluate intra-day (test) and inter-day (re-test) reliability of surface electromyography (sEMG) signals of the masseter and temporal muscles in patients with Down syndrome (DS). We determined the reliability of sEMG variables in 33 patients with DS. EMG signals were recorded at rest as well as during maximum voluntary clenching and maximum habitual intercuspation (MHI). The signals were analyzed considering the amplitude in the root mean square (RMS), mean frequency (MNF), median frequency (MDF) and approximate entropy (ApEn). The intraclass correlation (ICC2,1) for the three trials recorded during MHI in the two sessions (test and retest) revealed excellent intra-session and inter-session reliability (ICC2,1 = 0.76 to 0.97) for all sEMG variables and muscles. In the rest position, excellent reliability was found for RMS and ApEn (ICC2,1 = 0.75 to 1.00) and good to excellent reliability was found for MDF and MNF (ICC2,1 = 0.64 to 0.93). The intra-session (test) and inter-session (re-test) analyses demonstrated the reliability of nonlinear sEMG variables of the masticatory muscles in adults with Down Syndrome.